Perhitungan Terhadap Penentuan Sistem Pembuangan Genangan Pada Badan Jalan Di Jalan Perdagangan Kecamatan Banjarmasin Utara Kota - Novianti, Trie Rezky (CV. SINAR HOWUHOWU, 2026)
Perdagangan Street, located in Alalak Utara Village, Banjarmasin Utara District, Banjarmasin City, serves as an important connecting route between the HKSN Housing Complex and Brigjen Hasan Basri Street. The high traffic intensity in this area makes the road condition vital for community mobility. However, flooding caused by heavy rainfall has significantly damaged the road surface and negatively impacted the surrounding residential environment. This study was conducted to analyze and determine an effective drainage system for water disposal along the road. The method involved field observations, identification of flood-prone points, and technical calculations of the required drainage capacity. The findings indicate that flooding occurs due to limited existing drainage channels, insufficient capacity, and the absence of an integrated water disposal system with the surrounding environment. Through technical calculations, a new drainage system design was proposed to optimize rainwater flow into the main disposal channels. The implementation of this system is expected to reduce flooding, extend the lifespan of the pavement, and improve comfort and safety for both residents and road users. Thus, this research provides a practical contribution to improving residential road infrastructure while creating a healthier and more livable environment.